A-site cation engineering of cesium and MAPb0.5Sn0.5I3 perovskite: the properties and optoelectronic performance analysis using DFT calculations - Manala Tabu Mbumba; John Mahona; Joseph Kihedu; Salum K. Chang’waro; Geoffrey R. John (SN Applied Sciences, 2023)
Abstract Here, the first-principle calculations with the density functional theory calculations with PBE exchange–correlation functional were employed in investigating the effect of Cesium in the properties and optoelectronic performance of MAPb0.5Sn0.5I3 perovskite using A-site cation engineering technique. The control and Cesium based perovskites were generated and computed through CASTEP analysis from Material studio to determine their properties as well as optoelectronic performance. The findings revealed an improved properties of Cesium added perovskite compared to control ones. However, above 15%Cesium, phase separation was seen which declined the quality of the perovskite films. Moreover, simulation results of perovskites added with Cesium to 15% have demonstrated to have an improved optoelectronic performance as well as thermal stability by maintaining about 76% compared to the control which can retain about 39% of their initial power conversion efficiency after 15 days of aging at 85 °C in the ambient condition. This research presents a viable approach to investigate the impact of cation composition tuning on band gap, which can be extended to other perovskites. Additionally, it offers a broad set of design guidelines prior experiments for attaining a targeted band gap and modifying perovskite crystallization to enhance the characteristics, thermal stability, and optoelectronic performance of perovskite solar cells.